Culture of human labial mucosal epithelial cell for use in patients with bilateral limbal stem cell deficiency - S. A. Borzenok; M. Yu. Gerasimov; D. S. Ostrovskiy; B. E. Malyugin (Вестник трансплантологии и искусственных органов)
Aim: to obtain a stable population of the human labial mucosal epithelium without feeder cells through explant culture technique and simplified formulation of the culture media.Materials and methods. Labial mucosa samples were obtained from 6 patients in the operating room after the patients had signed an informed consent. Samples were trimmed of the substantia propria and cut into uniformed explants. Cell culture was done using DMEM/F12 (1:1) (1.05 mM calcium) and EpiLife (0.06 mM calcium) media, supplemented with 5% fetal bovine serum, antibioticantimycotic, insulin (5 μg/mL), hydrocortisone (5 μg/mL) and epidermal growth factor (10 ng/mL). Primary cells were stained for stemness and proliferative markers (anti-p63), intermediate filaments (anti-vimentin), and tight junction protein-1 (anti-ZO-1). Image analysis was performed in Fiji (ImageJ).Results. Primary cell culture was obtained from all the samples in both media. Cellular morphology was characterized as a classic “coble-stone” phenotype. 34.7% p63-expressing cells (median, n = 3) was detected in the 1.05 mM Ca medium, while ZO-1 expression was estimated at 17.05 μm per cell (median, n = 3). In cells cultured in 0.06 mM Ca medium, positive p63 expression was 39.2% (median, n = 3), while the length of the ZO-1 expression was 5.18 μm per cell (median, n = 3).Conclusion. This study presents a detailed protocol on how to obtain cell culture of human labial mucosal epithelium from a small biopsy with high proliferative activity without feeder cells condition. The 1.05 mM Ca medium promoted generation of the tight junction and may be used in in vitro epithelium differentiation models. In contrast, the 0.06 mM Ca medium maintained reduced level of maturation in the cell culture. Thus, the media formulations, cell culture source and method described in this study, may be used for transplantation of autologous labial mucosal epithelium in patients with bilateral limbal stem cell deficiency.